Estrategia de contravisualidad del cine colombiano en la película Matar a Jesús (Mora Ortega, 2018) - Hurtado Cadavid, John Jaime (2025)
This text argues that Killing Jesus, directed by Laura Mora Ortega (2018), represents a break from the tradition that confines Colombian cinema to narratives of violence, a tradition that has consolidated a visual regime stereotyping Colombian people. First, it presents a comparative analysis of Colombian films from the past three decades to highlight Mora’s unique narrative approach. Then, it conducts a textual analysis to reveal how her cinematic language proposes a countervisuality regime that exposes the formation of new subjectivities capable of challenging viewers to reflect on possible responses to the presence of evil in their environment. Thus, it analyzes how Mora Ortega uses the urban landscapes of a marginalized city and the relationships between victims and perpetrators to explore dynamics of grief, resilience, and the formation of new subjectivities that reject revenge as a moral response to harm.